1997
DOI: 10.1128/jvi.71.1.307-313.1997
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of simian immunodeficiency viruses from West African green monkeys: evidence of multiple genotypes within populations from the same geographical locale

Abstract: High simian immunodeficiency virus (SIV) seroprevalence rates have been reported in the different African green monkey (AGM) subspecies. Genetic diversity of these viruses far exceeds the diversity observed in the other lentivirus-infected human and nonhuman primates and is thought to reflect ancient introduction of SIV in the AGM population. We investigate here genetic diversity of SIVagm in wild-living AGM populations from the same geographical locale (i.e., sympatric population) in Senegal. For 11 new strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 61 publications
0
5
1
Order By: Relevance
“…Until recently, it was believed that all SIV infections were common and widespread in their hosts, but in a recent study we showed that SIV prevalence can vary significantly from one species to another (Aghokeng et al, 2006). Mustached and greater spot-nosed monkeys were species in which we found a very low SIV prevalence (about 3-4%), approximately ten times lower than prevalence rates observed in African green monkeys, sooty mangabeys, mandrills, and mantled guerezas (Apetrei et al, 2005;Bibollet-Ruche et al, 1997;Courgnaud et al, 2001;Jolly et al, 1996;Santiago et al, 2005;Souquiere et al, 2001;Takehisa et al, 2001). This estimate of low prevalence is reinforced by the work presented here.…”
Section: Discussioncontrasting
confidence: 55%
“…Until recently, it was believed that all SIV infections were common and widespread in their hosts, but in a recent study we showed that SIV prevalence can vary significantly from one species to another (Aghokeng et al, 2006). Mustached and greater spot-nosed monkeys were species in which we found a very low SIV prevalence (about 3-4%), approximately ten times lower than prevalence rates observed in African green monkeys, sooty mangabeys, mandrills, and mantled guerezas (Apetrei et al, 2005;Bibollet-Ruche et al, 1997;Courgnaud et al, 2001;Jolly et al, 1996;Santiago et al, 2005;Souquiere et al, 2001;Takehisa et al, 2001). This estimate of low prevalence is reinforced by the work presented here.…”
Section: Discussioncontrasting
confidence: 55%
“…For many years, it has been recognized that AGMs and sooty mangabey monkeys are chronically infected with SIV in the wild and, while these viruses cause no disease in their natural host, they produce an immunodeficiency syndrome when transmitted to rhesus or pigtailed macaques (3,7,19,32,35,49). It is interesting that the AGM population harbors a CCR5 allele which contains the D13N mutation, which plays an important role in CD4-independent SIV infection (39).…”
Section: Discussionmentioning
confidence: 99%
“…7). These results are potentially interesting since sooty mangabeys and African green monkeys become chronically infected with SIV but do not progress to simian AIDS (3,7,49).…”
Section: Figmentioning
confidence: 99%
“…There is evidence that AGMs have been infected with SIV agm since ancient times and that SIV agm viruses have become highly diverse (2,7,24,25,28,32). Indeed, AGMs have been classified into four geographically distinct subspeciesvervets (Cercopithecus aethiops pygerythrus), tantalus (Cercopithecus aethiops tantalus), grivets (Cercopithecus aethiops aethiops), and sabaeus (Cercopithecus aethiops sabaeus)-and each subspecies is naturally infected at a very high prevalence by a distinct strain of SIV agm without apparent immunodeficiency (2,7,32,33). Moreover, SIV agm isolates are approximately equally divergent from SIV mac251 and HIV-1 (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…It is not known whether coreceptors serve as attachment sites to strengthen virus adhesion or whether their roles are more complex, nor is it known whether CCR5 polymorphisms occur in nonhuman primates such as African green monkeys (AGMs) (Cercopithecus aethiops) that appear to have been infected with immunodeficiency viruses since ancient times (2,7,24,25,28,32). Recent studies of CCR5 chimeras have suggested that multiple extracellular regions contribute to infections by macrophage-tropic isolates of HIV-1 and that no single region is essential (4,8,34,38).…”
mentioning
confidence: 99%